A Juxta-Articular Myxoma of the Thumb in a young male: A case report - Tripathi, Sudhanshu Vinay; Khurram, Mohammad Fahud; Ahmed, Murad; Chaudhury, Gautam (Journal of Society of Surgeons of Nepal, 2023)
Juxta-articular myxomas are benign tumours that are most commonly associated with larger joints. Cases involving hand have been rarely reported till date. We present a case of a juxta-articular myxoma at the metacarpophalangeal joint of the thumb in a 30-year-old male patient. The preoperative diagnostic work-up included ultrasound and X-ray of left hand. The histopathological examination of the resected tumor confirmed the diagnosis. Follow-up ultrasound six months after surgery revealed no obvious recurrence. At 6 months, the patient had full range of motion without pain.